Retrospective analysis of enzootic bovine leucosis spread in Republic of Dagestan considering natural and climatic conditions - A. R. Mustafayev; M. O. Baratov (Ветеринария сегодня, 2023)
Retrospective analysis of enzootic bovine leucosis (EBL) data received by the Republic of Dagestan Veterinary Laboratory and Veterinary Department of the Republic of Dagestan was made. From 1988 to 2022, the Republican veterinary laboratories serologically tested3,205,118 animal sera for the antibodies to bovine leukaemia virus (BLV) antigen, and 76,133 (2.4%) of them were positive. High BLV infection levels were detected in 1988 (32.2%), 1989 (21.3%), 1991 (23.3%), 1993 (23.0%), 2005 (24.2%), 2010 (23.0%), and the lowest ones were reported in the recent years: 2020 – 1.0%, 2021 – 1.0%, 2022 – 0.5%. In2022, diagnostic testing of 875,312 serum samples was carried out, which included 476,493 sera collected from bovines in high-altitude and mountainous areas of Dagestan. In the plain areas, 255,312 bovine animals were tested for leucosis, and 122,967 animals were tested in the sub-mountain areas. The animal infection with BLV in these natural and climatic conditions was reported as follows: high-altitude and mountainous areas– 0.5% (2,313 animals), plain areas– 0.8% (1,925 animals), sub-mountain areas– 0.1% (109 animals). Additional 20,540 serum samples were tested in the laboratories at the transhumance pasture veterinary units, and 170 BLV seropositive animals (0.83%) were detected. No EBL was diagnosed in the laboratories of the Derbent, Kochubeysk, Ulankholsk, Bakressk veterinary units, but other four laboratories detected high level of BLV seropositive animals (Kizlyarsk– 14.6%, Babayurt – 3.6%, Tarumovsk– 3.0%, Kyzylyurt– 1.06%). Thus, EBL is widespread in animals, especially in the plain areas of the Republic of Dagestan.